Budget planning and control systems - Amey, Lloyd R. (Marshfield, Mass. : Pitman Pub., 1979)
This book is concerned with some aspect of business budgeting or budgetary control: the first two with the former, the remaining six with the latter. (The final chapter is a summing up)
Includes bibliographical references and indexes.
hza 17/09/2018
Loans
Keywords: Budget in business